Using psychophysiological measures to estimate dimensions of emotion in hedonic experiences. (October 2018) - Maia, Camila L.B.; Furtado, Elizabeth S.
Highlights: Significant correlation between emotion valence and variation of heart rate. Significant correlation between the number of user's mistakes in a game and GSR. Statistical correlation between arousal of emotion and low alpha, not significant. Abstract: In recent years, researchers have been interested in how emotional factors manifest during user system interactions. One example of this topic is the use of psychophysiological sensors as a complementary way to measure user's emotions with hedonic applications. Some psychophysiological measures have already been correlated with both valence and arousal, the main dimensions of emotion. However, a consensus has not been reached on which psychophysiological measure better represents the dimensions of emotion. This study presents three combined non-invasive psychophysiological measures that were used to verify which better represents the dimensions of emotion. An experiment was conducted using quantitative and qualitative data analysis, and the results were: a significant correlation between valence and variation of heart rate, and between arousal and alpha band. The results are relevant to fields interested in the analysis of human behavior in interacting situations, since they can help design experiments that consider user emotions.